Influence of attention deficit hyperactivity disorder (ADHD) on the teaching-learning process of third grade students BGU - Coello Paredes, Allison del Pilar; Navarrete Mera, Manuel Adriel (Revista Minerva, 2022)
Attention deficit hyperactivity disorder, also known as ADHD, affects the individual’s abilities to be able to develop new skills and abilities, which allow the construction of their own knowledge, so that after what was previously described, it was established as the main objective , the collection of data and information on the influence of this disorder in adolescents during the teaching-learning process, for the development of the process of the silver objective, the bibliographic method was applied, tending as the main source contemporary works about this disorder and its incidence in the teaching-learning process, this allowed the compilation of several conceptual categories in different perspectives, from the world reality in which ADHD is found, in contrast to the substantivity in the Ecuadorian educational context, tending as a conclusive result the need of a teaching-learning process I Immersed in playful strategies that facilitate the development of students’ abilities, skills and abilities.